2012
DOI: 10.1002/we.1528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric stability on wind turbine loads

Abstract: Simulations of wind turbine loads for the NREL 5 MW reference wind turbine under diabatic conditions are performed. The diabatic conditions are incorporated in the input wind field in the form of wind profile and turbulence. The simulations are carried out for mean wind speeds between 3 and 16 m s  − 1 at the turbine hub height. The loads are quantified as the cumulative sum of the damage equivalent load for different wind speeds that are weighted according to the wind speed and stability distribution. Four si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 42 publications
(69 reference statements)
9
127
0
Order By: Relevance
“…Gryning et al (2007) found that for a two-year period, easterly surface winds agreed well with the observations using the ψ m expressions of Dyer (1974). Similarly, Peña (2009) and Sathe et al (2013) found that commonly used expressions for ψ m suited the easterly surface wind profile for a range of stability classes based on four years of data. These works show that the diabatic wind profile is accurate in describing the vertical wind shear up to a height that depends on the stability of the surface layer, for very unstable and stable conditions up to 160 and 40 m, respectively.…”
Section: Surface Layermentioning
confidence: 62%
See 1 more Smart Citation
“…Gryning et al (2007) found that for a two-year period, easterly surface winds agreed well with the observations using the ψ m expressions of Dyer (1974). Similarly, Peña (2009) and Sathe et al (2013) found that commonly used expressions for ψ m suited the easterly surface wind profile for a range of stability classes based on four years of data. These works show that the diabatic wind profile is accurate in describing the vertical wind shear up to a height that depends on the stability of the surface layer, for very unstable and stable conditions up to 160 and 40 m, respectively.…”
Section: Surface Layermentioning
confidence: 62%
“…These results demonstrate the close connection between the wind profile and the turbulence structure. Sathe et al (2013) re-derived the Mann model parameters to estimate the impact of turbulence under different stabilities on turbine loads. By including stability effects, they found that the loads on a number of turbine components increased up to 17% compared to the neutral case.…”
Section: Traditional Anemometry-based Studiesmentioning
confidence: 99%
“…In a following study, Kelley (2011) detected that the maximum turbine damages occurred within a narrow range of atmospheric stability usually associated with LLJs. Sathe et al (2013) used wind profile models together with an aeroelastic simulator to investigate whether the wind profile and the atmospheric stability modify the wind turbine loads. They found that loads at different turbine parts were affected slightly by the wind profile (up to 7 %) and significantly by the atmospheric stability (up to 17 %).…”
Section: Previous Work On Wind Shearmentioning
confidence: 99%
“…Most of wind projects are developed based on the mean wind speed at the hub height of the turbine without any consideration of atmospheric stability effect. However, significant dependence of wind resource on this stability issue has been recognized [1,2]. Stability is linked to the influence of the thermal effects.…”
Section: Introductionmentioning
confidence: 99%